2005
DOI: 10.1128/jcm.43.3.1301-1303.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Easy-Flow Copan Liquid Stuart's and Starplex Swab Transport Systems for Recovery of Fastidious Aerobic Bacteria

Abstract: Because samples are frequently submitted on swabs from distant sites, viability of the organism must be maintained. We compared two transport systems, a new Copan Liquid Stuart's swab with an Easy-Flow swab applicator and the Starplex Liquid Stuart's swab. The purpose of the study was to assess the release and/or recovery of organisms from the Copan system compared to that from Starplex. Triplicate swabs were seeded with 3 dilutions of Neisseria gonorrhoeae, Neisseria meningitidis, Haemophilus influenzae, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
31
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 1 publication
1
31
1
Order By: Relevance
“…In a previous study, a Copan swab with liquid Stuart's was reported to release more organisms than a Starplex liquid Stuart's swab, based on consistently higher time zero CFU recovered (Drake et al, 2005). However, there was no indication as to how this correlated with the actual number of organisms released.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In a previous study, a Copan swab with liquid Stuart's was reported to release more organisms than a Starplex liquid Stuart's swab, based on consistently higher time zero CFU recovered (Drake et al, 2005). However, there was no indication as to how this correlated with the actual number of organisms released.…”
mentioning
confidence: 90%
“…Swab transport devices should be able to maintain the viability of microorganisms present, and the swab should allow for release of a sufficient representative portion of the specimen material and preserve the integrity of nucleic acids for amplification testing. Limited studies describe organism or specimen release from swabs in transport systems (Drake et al, 2005;Österblad et al, 2003;Roelofsen et al, 1999).Most swab collection devices currently on the market are prepared with rayon or Dacron fibers wound onto the tip of the swab shaft. The new ESwab (Copan Diagnostics, Murrieta, CA) is a nylon-tipped swab prepared by spray-on flocked fiber technology that potentially results in better specimen collection and a more efficient release of specimen material with less specimen entrapment than woven fibertipped swabs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing frequency of transport delays due to cost containment measures, consolidations, and services being shifted to centralized or reference laboratories, robust transport systems are becoming increasingly relevant. The CLSI M40-A method (2) was used recently to evaluate several swab collection and transport devices for maintenance of bacteria viability (3,4,6,7,8,9).Swab tips, which are typically rayon or Dacron, should be prepared with material that collects sufficient specimen material, is nontoxic to microorganisms, maintains viability in conjunction with the transport medium, and releases specimen material efficiently onto agar media. A new nylon-tipped swab (ESwab; Copan Diagnostics, Inc., Corona, CA) prepared by spray-on flocked fiber technology has been developed for transport of bacteria and viruses.…”
mentioning
confidence: 99%
“…In: Proceedings of the 99th general meeting of the American Society for Microbiology, Chicago, IL). 4,5,9,[11][12][13][14][16][17][18][19][20][21] Frozen semisolid or liquid transport media can maintain bacterial viability for days. 2,6,7,15 The viability of Bacteroides sp.…”
mentioning
confidence: 99%